The Chief Registrar role in the UK: leadership capacity and development of hybrid leaders. Issue 1 (23rd January 2020) - Snelling, Iain; Exworthy, Mark; Ghezelayagh, Shahin
Abstract : Purpose: The purpose of the study is to evaluate the first cohort of the Royal College of Physicians' (RCP) Chief Registrar programme in 2016/7. Chief Registrars provide medical leadership capacity through leadership development posts. Design/methodology/approach: The study adopted a mixed methods design, comprising a monthly survey of the 21 Chief Registrars in the first cohort, interviews with Chief Registrars, and six cases studies where Chief Registrars and colleagues were interviewed. Findings: Chief Registrars enjoyed high levels of practical, professional, and leadership support from their employing organisations, the RCP, and the Faculty of Medical Leadership and Management. They had high degrees of autonomy in their roles. As a result, roles were enacted in different ways, making direct comparative evaluation problematic. In particular, we identified variation on two dimensions: first, the focus on medical leadership generally, or quality improvement more specifically, and second, the focus on personal development or organisational leadership capacity. Research limitations/implications: The data are limited and drawn from the first cohort's experience. The Chief Registrar scheme, unlike many other leadership fellowships, maintains a high level of clinical practice (with a minimum 40 per cent leadership work). This suggests a clearer preparation for future hybrid leadership roles. Practical implications: This paper may offer some support and guidance for Chief Registrars and those who work with and support them. Originality/value: This study adds to the literature on leadership development for doctors in hybrid roles, and highlights the distinctiveness of the scheme compared with other schemes.